Integrating Good Manufacturing Practices, Lean Manufacturing, and Information Technology for Operational Excellence in Indonesian Food SMEs - Ahmad Syafruddin Indrapriyatna; Reinny Patrisina; Asi Siva Dea; Nahda Sulasi; Yonithri Sherlyna (Jurnal Nasional Teknologi dan Sistem Informasi, 2025)
Small and medium-scale food industries, despite their crucial role in regional economic development, face significant challenges related to hygiene, inefficiency, and process waste. This study, based on three case studies from IKM Kerupuk Janek Arsyila, IKM Kerupuk Buk Ita, and UMKM Kue Bawang Medan “Rizka” in West Sumatra, identifies key issues such as inefficient layouts, weather dependency, lack of standardized procedures, and low adherence to cleanliness standards. The study integrates Good Manufacturing Practices (GMP) for hygiene evaluation and Lean Manufacturing tools—such as Waste Assessment Model (WAM), Value Stream Mapping (VSM), VALSAT, and fishbone diagrams—to identify and reduce waste. Additionally, Information Technology (IT) is introduced as an enabler to strengthen monitoring, data collection, and documentation. Simple digital tools such as production dashboards, mobile-based hygiene checklists, and IoT-assisted sensors can facilitate real-time supervision and improve GMP compliance. Findings reveal that dominant wastes include transportation, motion, defects, and waiting, with initial Process Cycle Efficiency (PCE) ranging from 41% to 65%. After improvements involving layout redesign, drying machines, digital recordkeeping, and the 5S principles, PCE increased to 81%–95%. This study demonstrates that the integration of Lean–GMP and digital tools can significantly enhance production efficiency, hygiene standards, and sustainability in Indonesian food SMEs.